Techno-Economic Models for Optimised Utilisation of Jatropha curcas Linnaeus under an Out-Grower Farming Scheme in Ghana - Isaac Osei; Joseph O. Akowuah; Francis Kemausuor (Resources, 2016)
Techno-economic models for optimised utilisation of jatropha oil under an out-grower farming scheme were developed based on different considerations for oil and by-product utilisation. Model 1: Out-grower scheme where oil is exported and press cake utilised for compost. Model 2: Out-grower scheme with six scenarios considered for the utilisation of oil and by-products. Linear programming models were developed based on outcomes of the models to optimise the use of the oil through profit maximisation. The findings revealed that Model 1 was financially viable from the processors’ perspective but not for the farmer at seed price of $0.07/kg. All scenarios considered under Model 2 were financially viable from the processors perspective but not for the farmer at seed price of $0.07/kg; however, at seed price of $0.085/kg, financial viability was achieved for both parties. Optimising the utilisation of the oil resulted in an annual maximum profit of $123,300.